Triple network activation causes tinnitus in patients with sudden sensorineural hearing loss: A model-based volume-entropy analysis - Lee, Seung Jae; Park, Jaemin; Lee, Sang-Yeon; Koo, Ja-Won; Vanneste, Sven; De Ridder, Dirk; Lim, Seonhee; Song, Jae-Jin (Frontiers in Neuroscience, 2022)
Tinnitus can be defined as the conscious perception of phantom sounds in the absence of corresponding external auditory signals. Tinnitus can develop in the setting of sudden sensorineural hearing loss (SSNHL), but the underlying mechanism is largely unknown. Using electroencephalography, we investigated differences in afferent node capacity between 15 SSNHL patients without tinnitus (NT) and 30 SSNHL patients with tinnitus (T). Where the T group showed increased afferent node capacity in regions constituting a “triple brain network” [default mode network (DMN), central executive network (CEN), and salience network (SN)], the NT group showed increased information flow in regions implicated in temporal auditory processing and noise-canceling pathways. Our results demonstrate that when all components of the triple network are activated due to sudden-onset auditory deprivation, tinnitus ensues. By contrast, auditory processing-associated and tinnitus-suppressing networks are highly activated in the NT group, to overcome the activation of the triple network and effectively suppress the generation of tinnitus.